2022
DOI: 10.3389/fimmu.2022.895501
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin B Receptor Immunodynamics in Pulmonary Arterial Hypertension

Abstract: IntroductionInflammation is a major pathological feature of pulmonary arterial hypertension (PAH), particularly in the context of inflammatory conditions such as systemic sclerosis (SSc). The endothelin system and anti-endothelin A receptor (ETA) autoantibodies have been implicated in the pathogenesis of PAH, and endothelin receptor antagonists are routinely used treatments for PAH. However, immunological functions of the endothelin B receptor (ETB) remain obscure.MethodsSerum levels of anti-ETB receptor autoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Results were reported using a positive cut-off at ≥20 RU/ml. Anti-AT 1 R and Anti-ET A R antibody serum levels were measured by ELISA (CellTrend GmbH, Luckenwalde, Germany [since 2012, One Lambda, Inc., Canoga Park, CA]) as described ( 24 ), analogously to anti-ET B receptor autoantibody quantification performed earlier in a partially overlapping cohort ( 44 ).…”
Section: Methodsmentioning
confidence: 99%
“…Results were reported using a positive cut-off at ≥20 RU/ml. Anti-AT 1 R and Anti-ET A R antibody serum levels were measured by ELISA (CellTrend GmbH, Luckenwalde, Germany [since 2012, One Lambda, Inc., Canoga Park, CA]) as described ( 24 ), analogously to anti-ET B receptor autoantibody quantification performed earlier in a partially overlapping cohort ( 44 ).…”
Section: Methodsmentioning
confidence: 99%
“…Anti-AT 1 R and Anti-ET A R antibody serum levels were measured by ELISA (CellTrend GmbH, Luckenwalde, Germany [since 2012, One Lambda, Inc., Canoga Park, CA]) as described 24 , analogously to anti-ET B receptor autoantibody quantification performed earlier in a partially overlapping cohort. 44…”
Section: Methodsmentioning
confidence: 99%
“…In addition to its vasoactive properties, ET-1 plays an important role in modulating several inflammation pathways, both directly, by inducing the migration of neutrophils and monocytes [ 26 , 27 ], and indirectly, by increasing the production of inflammatory cytokines [ 28 ] and adhesion molecules in different cell types [ 29 , 30 ]. A recent study on ETBR immunodynamics highlighted the presence of a regulatory feedback of the effect of ET-1 on immune cells: ETBR deficiency in engineered mice led to PAH, pulmonary vascular hyperresponsiveness and right ventricular hypertrophy with lymphocytic alveolitis and marked lymphocytic perivascular infiltrate, suggesting that ETBR-mediated signalling pathways may have an immunomodulatory effect [ 31 ]. Increased ET-1 levels have been found in the serum and in the lungs of IPAH patients [ 32 , 33 ].…”
Section: Endothelial Dysfunctionmentioning
confidence: 99%
“…Guo et al [ 117 ] demonstrated higher titres of anti-ETAR antibodies in SLE patients complicated by PAH vs. those in SLE patients without PAH (41.5% vs. 17.1%, respectively), with a correlation between the anti-ETAR titres and the sPAP value measured by echocardiography and RHC. A recent study evaluated the prevalence of anti-ETBR antibodies in SSc patients, finding more elevated serum levels in SSc-PAH patients vs. those of healthy controls [ 31 ]; given the immunomodulatory role of ETBR , it could be hypothesised that these autoantibodies can block its downstream signalling pathway, thus enhancing inflammation, but more studies are required to ascertain their exact pathogenetic role.…”
Section: Autoimmunitymentioning
confidence: 99%